Exploring writing anxiety in analytical exposition text: A gender-based study of Indonesian high school EFL learners - Ichwany, Salsabila Saifa Fitra; Cahyono, Bambang Yudi (Journal on English as a Foreign Language, 2025)
Students often experience writing anxiety due to limited knowledge and skills in completing writing tasks. Although widely studied, little research has addressed writing anxiety in composing analytical exposition texts among high school students. This study investigated the students’ levels, types, and causes of writing anxiety across gender. It was conducted at one public school in Malang City, Indonesia, and involved 114 eleventh graders. Data were collected using the Second Language Writing Anxiety Inventory (SLWAI) and the Causes of Writing Anxiety Inventory (CWAI). Data were analyzed by using descriptive quantitative analysis and inferential statistics. Findings revealed moderate to high anxiety levels in both gender. Female students’ average score (49.78) was slightly higher than male students (45.79). Statistical difference was found in levels of anxiety across gender. Furthermore, female and male students faced cognitive anxiety, somatic anxiety, and avoidance behavior. Somatic anxiety was at moderate to low levels; however, both groups experienced moderate to high cognitive anxiety and avoidance behavior. Meanwhile, female and male students suffered from anxiety due to linguistic difficulties, fear of evaluation, and insufficient writing practice. These results underscore the need for explicit instruction on linguistic features, constructive feedback, and regular writing practice to reduce students’ anxiety.